The long 19th century : European history from 1789 to 1917 - Weiner, Robert I.; Teaching Company (Chantilly, Va. : Teaching Co., 2005)
Europe's 19th century, is often broadly defined as the period from the French Revolution to World War I, forming the foundation of the modern world. The course moves from the impact of both the French and Industrial Revolutions in the period from 1789-1848, into the so-called "unifications" of Italy and Germany in the 1850s and 1860s, followed by the spread of industrialism and nationalism into the furthest reaches of Europe toward the end of the century. The discussion provides a basis to understand this turbulent era and its effect on peasants, workers, the middle class, aristocrats, women, and minorities.
Lecture 1. The long 19th century -- Lecture 2. The legacy of the past, the old regime -- Lecture 3. The age of revolution, 1789-1848 -- Lecture 4. The French Revolution -- Lecture 5. The Napoleonic Era, 1799-1815 -- Lecture 6. The first industrial revolution, 1760-1850 -- Lecture 7. The Era of Metternich, 1815-1848 -- Lecture 8. The revolutions of 1848 -- Lecture 9. Europe, 1850-1871, an overview -- Lecture 10. The Crimean War, 1853-1856 -- Lecture 11. From Napoleon to Napoleon, France, 1815-1852 -- Lecture 12. Napoleon III, an evaluation -- Lecture 13. Italy on the eve, an overview -- Lecture 14. Cavour and Napoleon III, "unifying" Italy -- Lecture 15. Germany on the eve -- Lecture 16. Age of Bismarck, creating the German Empire -- Lecture 17. The British way -- Lecture 18. The Russian experience, 1789-1881 -- Lecture 19. The apogee of Europe, 1870-1914 -- Lecture 20. The industrialization of Europe -- Lecture 21. The socialist response -- Lecture 22. The longest hatred, European anti-semitism -- Lecture 23. England, 1868-1914, liberalism to democracy -- Lecture 24. The Third Republic, France, 1870-1914. -- Lecture 25. Bismarckian and Wilhelminian Germany -- Lecture 26. Flawed states, Austria-Hungary and Italy -- Lecture 27. Russia, Turkey, and the Balkans -- Lecture 28. Bismarck dominates Europe, 1870-1890 -- Lecture 29. The "new" imperialism -- Lecture 30. The diplomacy of imperialism, 1890-1907 -- Lecture 31. Europe in crisis, 1908-1914, outbreak of war -- Lecture 32. The origins of World War I -- Lecture 33. The Great War, a military overview -- Lecture 34. The home front during total war -- Lecture 35. The impact of World War I, new world disorder -- Lecture 36. Looking back, thinking ahead.
Compact discs.
In three containers (23 cm.).
Robert I. Weiner, lecturer, Lafayette College.
Keywords: Europe -- History -- 1789-1900.; Europe -- History -- 20th century